INDICATORS AND METHODS FOR ASSESSING INTERBANK COMPETITION ENVIRONMENT: THE CASE OF UZBEKISTAN BANKING SECTOR - Madina Ataboyevna Ataboyeva (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2026)
This article provides comprehensive analysis of indicators and methods for assessing the interbank competition environment in Uzbekistan's banking sector based on empirical data from 2020-2024.